Daily activity limitations and physical activity encouragement influence adolescents seeking health care for neck and low back pain - Oliveira, Crystian B. [UNESP]; Pinto, Rafael Z.; Damato, Tatiana M. [UNESP]; Lemes, Italo Ribeiro; Delfino, Leandro D. [UNESP]; Tebar, William R. [UNESP]; Christofaro, Diego G.D. [UNESP] (Elsevier, 2021)
Background: Understanding the factors associated with care-seeking behaviour in adolescents with spinal pain will inform health care professionals and guide a better decision-making. Objective: To identify factors, including parents’ habits and behaviour, related to care-seeking in adolescents with neck pain or low back pain (LBP). Study design: A cross-sectional study. Methods: Adolescents between 10 and 17 years were randomly recruited from public schools. The proportion of adolescents with neck or LBP and those who had sought care for neck and LBP were assessed with the Nordic Musculoskeletal questionnaire. Daily activity limitation and the frequency of parents' habits and behaviour were collected using self-reported questions. Logistic regression analyses were performed to investigate if the following factors were associated with adolescents’ care-seeking behaviour due to neck or LBP: daily activity limitations, physical activity (PA) domains, items of the social support scale. Results: The prevalence of adolescents reporting neck or LBP was 31.4% (318 out of 1011). Of these, 35.8% (n = 114) sought care for neck or low back pain. Activity limitations related to neck or LBP (OR: 5.83, 95% CI: 3.46 to 9.84), higher PA levels at school (OR: 1.67, 95% CI: 1.02 to 2.75), and PA encouragement (OR: 2.73, 95% CI: 1.27 to 5.85) were associated with care-seeking in adolescents with neck or LBP. Conclusion: Adolescents with activity limitations due to neck or LBP, higher PA levels at school and encouraged by parents or friends to practice PA were more likely to seek care for their neck or LBP.
Keywords: low back pain; Neck pain; Seeking care